The Effect of Organic Fertilizer of Goat Urine and NPK on the Growth of Long Bean Plant (Vigna sinensis L.) - Sapril, Dian Islamiaty; Raksun, Ahmad; Zulkifli, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
One of the most popular vegetables is the long bean (Vigna sinensis L.). Due to the presence of Rhizobium bacteria nodules in its roots, long bean plants are considered soil enrichers. Liquid organic fertilizer from goat urine is highly soluble in soil and contains essential nutrients crucial for soil fertility. This study aims to ascertain the best fertilizer dose for plant development as well as the effects of goat urine organic fertilizer, NPK fertilizer, and their combination on the growth of long bean plants (Vigna sinensis L.). A completely randomized design was used to perform the study as an experiment (CRD). With the aid of SPSS for Windows 25, two-way ANOVA was used for data analysis. Post hoc analyses were performed using DMRT and were allowed if the p-value (sig) was less than 0.05 or if the computed F value was greater than the tabular F value. The combination of goat urine organic fertilizer (POC) and NPK fertilizer did not substantially alter the development of long bean plants, according to the findings of the ANOVA study on the plant height parameter. Significant variations were seen, nonetheless, for other metrics as chlorophyll content, wet and dry weights, leaf area, and number of leaves. At the 5% significance level, the impact of treatments on plant height metrics showed that either the alternative hypothesis, H1, or the null hypothesis, H0, was accepted. Thus, it can be said that there is a strong interaction between the growth of long bean plants and the combination of NPK fertilizer and goat urine organic fertilizer (POC).